Pemberdayaan Masyarakat Melalui Aksi Penanaman Pohon Sebagai Upaya Meningkatkan Partisipasi Dalam Konservasi Lingkungan Di Desa Puraseda Kabupaten Bogor - Afgan Fadilla; M. Chairil Akbar Setiawan; Abdullah Ahmad; Aldino Satrio Ferdinand; Muhammad Syawzy Alfaro (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Environmental degradation caused by deforestation and the decline of vegetation cover requires conservation efforts that actively involve local communities. One practical approach to environmental conservation is tree planting accompanied by environmental education. This community service program aimed to enhance community participation in environmental conservation through a tree-planting initiative in Puraseda Village, Bogor Regency. The implementation methods included preparation, coordination with the village government, educational sessions on deforestation and environmental conservation, participatory tree-planting activities, and evaluation through observation and group discussions. The program involved university students, village officials, and local residents, fostering collaboration in environmental conservation efforts. The results indicated that participants actively engaged in all stages of the program and demonstrated improved awareness of the importance of environmental conservation. In addition to contributing to ecological restoration through increased vegetation cover, the program strengthened collective environmental awareness and reinforced the spirit of community cooperation (gotong royong) in protecting the environment. Therefore, integrating tree-planting activities with environmental education represents an effective community empowerment approach to increasing public participation in sustainable environmental conservation.